Cláusulas espejo en el comercio internacional: desafíos y perspectivas para la agricultura europea - Alvares García Júnior, Armando (tirant lo blanch, 2025)
This study analyses the complexities and challenges of the so-called «mirror clauses» in EU trade agreements with third countries, a topic of great socio-economic and legal relevance. These clauses aim to ensure that imported products comply with the same standards applied in the European single market. The research contextualises mirror clauses within geopolitical and geoeconomic dynamics, differentiating them from other trade provisions. It explores their practical application and associated legal controversies at different levels of international and European law, analysing how they seek to balance standards between developed and developing countries. The study addresses the concept and application of mirror clauses from perspectives such as international relations, public international law, trade international law and private international law. It examines issues such as the law applicable to import contracts, the competent jurisdiction, and the EU legal framework for applying European standards to imported products. The theoretical benefits and practical limitations of these clauses are discussed, highlighting their importance in ensuring the uniform application of standards, although they face challenges due to disparities in implementation capacity between countries. It concludes that while mirror clauses are necessary to protect European consumers, their implementation must consider the capabilities and needs of exporting countries, especially those in development, and promote cooperation and technical assistance to improve their standards and control systems.
Mirror Clauses in International Trade: Challenges and Perspectives for European Agriculture
Este artículo ofrece un análisis jurídico, político y económico de las cláusulas espejo en los acuerdos comerciales internacionales de la Unión Europea, con énfasis en sus efectos sobre la agricultura europea. A través de un enfoque multidisciplinar, el texto examina la función de estas cláusulas como instrumentos de equidad regulatoria, sus implicaciones en la soberanía de los Estados exportadores, y el debate sobre su compatibilidad con los principios de la OMC. La investigación destaca tensiones entre sostenibilidad, desarrollo y proteccionismo, en el contexto de las recientes protestas agrarias y del proceso legislativo europeo.
Keywords: international trade; mirror clauses; regulatory standards; protectionism; reciprocity; development